Treatment of NASH with Antioxidant Therapy: Beneficial Effect of Red Cabbage on Type 2 Diabetic Rats. (30th September 2018) - Dal, Stéphanie; Van der Werf, Remmelt; Walter, Catherine; Bietiger, William; Seyfritz, Elodie; Mura, Carole; Peronet, Claude; Legrandois, Julie; Werner, Dalal; Ennahar, Said; Digel, Fabien; Elisa, Maillard-Pedracini; et al.
Abstract : Aims . Oxidative stress (OS) plays a major role in type 2 diabetes and its vascular and hepatic complications, and novel therapeutic approaches include natural antioxidants. Our previous chemical and biological studies demonstrated the antioxidant activities of red cabbage (RC), and here, we aimed to determine the in vivo effects of 2-month long RC consumption using a high-fat/high-fructose model of diabetic rats. Results . This vegetable, associated with lifestyle measurement, was shown to decrease OS and increase vascular endothelial NO synthase expression, ensuring vascular homeostasis. In the liver, RC consumption decreased OS by inhibiting p22phox expression and Nrf2 degradation and increasing catalase activity. It inhibited the activation of SREBP (1c, 2), ChREBP, NF- κ B, ERK1/2, PPAR γ, and GS and SIRT1 decrease, as observed in diabetic rats. Conclusion/innovation . RC consumption led to metabolic profile improvement, together with hepatic function improvements. Although lifestyle changes are not sufficient to prevent diabetic complications, enrichment with RC avoids progression hepatic complications. This antioxidant strategy using RC does not only able to increase antioxidant defense, such as classical antioxidant, but also able to assure a metabolic and energetic balance to reverse complications. Whereas traditional medical therapy failed to reverse NASH in diabetic patients, consumption of RC should be a natural therapy to treat it.